Adult and early‐stage characters of Brassolini contain conflicting phylogenetic signal (Lepidoptera, Nymphalidae). (21st February 2013) - PENZ, CARLA M.; FREITAS, ANDRE V. L.; KAMINSKI, LUCAS A.; CASAGRANDE, MIRNA M.; DEVRIES, PHILIP J.
Abstract : This study examines the contribution of early‐stages and adult characters to the reconstruction of the phylogeny of Brassolini butterflies. Parsimony analyses used both equal weights and implied weights, and a series of analyses were performed. First, we analysed adult and early‐stages partitions independently and in combination for a subset of 27 species; in these cases the matrices were mostly complete. Whereas the adult partition alone produced a topology that was well resolved and congruent with previous studies, the early‐stages partition produced a poorly resolved tree under equal weights. Furthermore, implied weights produced a well‐resolved early‐stages topology that differed significantly from the adult topology. When both partitions were combined for 27 species, implied weights yielded a topology that resembled the adult tree except for the positions of Bia and Penetes, but statistical node support was generally lower. This suggests that stochastic noise increased when early‐stage characters were added to the adult partition, but the combined partitions topology was not statistically different from that based on adult characters alone. Second, given that preserved early stages are not as readily available as adults, we analysed a matrix including 45 species in which early‐stage data were missing for 18 species, and compared the topology to that produced by the adult partition alone. Results were similar to the analyses including fewer species; the combined partitions tree was similar to that from the adult partition except for the position of Bia and Penetes . We compare our findings to other genus‐level phylogenetic studies within Lepidoptera that have also used early‐stages and adult characters.